Prospective Comparison of the AIMS65 Score, Glasgow-Blatchford Score, and Rockall Score for Predicting Clinical Outcomes in Patients with Variceal and Nonvariceal Upper Gastrointestinal Bleeding - Arunchai Chang; Chokethawee Ouejiaraphant; Keerati Akarapatima; Attapon Rattanasupa; Varayu Prachayakul (Korean Society of Gastrointestinal Endoscopy, 2021)
Background/Aims This study aimed to determine the performance of the AIMS65 score (AIMS65), Glasgow-Blatchford score (GBS), and Rockall score (RS) in predicting outcomes in patients with upper gastrointestinal bleeding (UGIB), and to compare the results between patients with nonvariceal UGIB (NVUGIB) and those with variceal UGIB (VUGIB). Methods We conducted a prospective observational study between March 2016 and December 2017. Receiver operating characteristic curve analysis was performed for all outcomes for comparison. The associations of all three scores with mortality were evaluated using multivariate logistic regression analysis. Results Of the total of 337 patients with UGIB, 267 patients (79.2%) had NVUGIB. AIMS65 was significantly associated (odds ratio [OR], 1.735; 95% confidence interval [CI], 1.148-2.620), RS was marginally associated (OR, 1.225; 95% CI, 0.973-1.543), but GBS was not associated (OR, 1.017; 95% CI, 0.890-1.163) with mortality risk in patients with UGIB. However, all three scores accurately predicted all other outcomes (all p<0.05) except rebleeding (p>0.05). Only AIMS65 precisely predicted mortality, the need for blood transfusion and the composite endpoint (all p<0.05) in patients with VUGIB. Conclusions AIMS65 is superior to GBS and RS in predicting mortality in patients with UGIB, and also precisely predicts the need for blood transfusion and the composite endpoint in patients with VUGIB. No scoring system could satisfactorily predict rebleeding in all patients with UGIB.